Edukasi Kesehatan dan Pertolongan Pertama Choking (Tersedak) Pada Siswa SMA Swasta Medan - Amila; Sembiring, Evarina; Sipayung, Normi Parida (PELITA NUSA TENGGARA, 2023)
Choking is an emergency event that often occurs in the community, especially among school students, therefore it is very necessary to educate and train students in handling choking, especially if the emergency occurs in the school area. The purpose of community service activities is to increase students' knowledge and skills in handling emergency choking events due to obstruction of foreign objects in the airway. The activity was carried out for Medan Private High School students. Prior to counseling, a pretest and posttest were carried out to determine students' understanding of the first aid in choking cases. Education is carried out through lectures, questions and answers, video, and demonstrations. The results of the pretest showed that the majority of knowledge about first aid for choking was lacking by 50% and the results of the posttest showed that the majority of knowledge was good by 55.6%. This community service activity is expected to increase students' knowledge and skills in the first handling of cases of choking due to obstruction of foreign objects in the airway.